Rapeseed and Pulses Demonstrations as Cultivation Push in District Ferozepur of Punjab - Gill, Jagjot Singh (Indian Journal of Extension Education, 2021)
Punjab Agricultural University Farm Advisory Service Centre, Ferozepur conducted total 361 demonstrations on PAU improved varieties SML 668 and SML 832 of summer moong, GPF 2 and PBG 5 varieties of gram (chickpea) and GSC 7 variety of gobhi sarson on farmer’s fields in district Ferozepur during three consecutive years from rabi 2016-17 to rabi 2018-19 with aim to get the farmers to grow pulses and rapeseed to secure access of farmer families to an appropriately nutritious diet comprising all essential nutrients and higher net return. Low yield of traditional or local varieties of pulses and rapeseed is a major concern for farmers. To manage the problem of lower yield of pulses and rapeseeddemonstration were conducted in different localities of Ferozpur district. PAU recommended varieties of Gobhi sarson, chickpea and summer moong gave 17.5, 19.3 and 17.5 per cent higher grain yield over local check grown by farmers. Chickpea green may earn higher netreturn of Rs. 304760 which is 83 and 78.7 per cent more than chickpea grain crop and wheat crop. Gobhi sarson with processing may earn net return of Rs. 111205.5 which is 47.6 and 41.7 per cent higher as compared to ghobi sarson without processing and wheat crop. Summer moong given additional net return of Rs. 93208 along with net return from rabi season previous crops like potato and gobhi sarson. Rapeseed and pulses gave higher net return than wheat crop along with nutritional security.